Scientometric analysis of the main thematic fields and keywords in the subject area «Public health, environmental and occupational health - Aksenova, E I; Tarkhov, K Yu (Problemy sotsial'noi gigieny, zdravookhraneniia i istorii meditsiny, 2023)
Research in the field of public health at the global, national, regional and organizational levels continue to be relevant, attracting attention of the researchers who find new aspects of various problems and issues for consideration and analysis in this area. The paper presents results of a scientometric analytical study of the publication landscape for 2019-2021 in the field of public health, using the analytical platform SciVal, the data source for which is the international scientific database Scopus. The study shows positive dynamics and steady growth in most scientometric indicators in the subject area under consideration during the study period. A structural-functional and semantic-linguistic analysis of the top-50 keywords was also carried out, which showed that their ranking position significantly depends on the choice of one of two indicators: either by the number of publications or by relevance. Publications on public health are characterized by a polythematic distribution, providing researchers with the opportunity to make a wide choice in conducting scientific research in the branches of medical science they are interested in, taking into account scientometric indicators characterizing the publication landscape in these areas.